BNCC e a educação antirracista: reflexões e apontamentos sobre o componente curricular artes - Silva, Pedro Henrique Pamplona (Universidade Federal de São Carlos, 2023)
This research aims to discuss Anti-racist Education in the National Common Curricular Base (BNCC) in the “Arts” Curricular Component, focusing on the early years of Elementary School. For this purpose, we will use the final version of the document approved in 2017 by the Ministry of Education (MEC). The research is a bibliographic, qualitative and documentary study from the perspective of Content Analysis and the principles of Communicative Methodology. Initially, we can point out that the Education for Ethnic-Racial Relations proposed by the BNCC does not offer subsidies and objective notes for an Anti-racist Education. In this sense, we justify the importance of research to understand how the BNCC articulates an Antiracist Education or if, in fact, the document's proposals make an Inclusive Education for Ethnic-Racial Relations unfeasible. As an initial theoretical support, we resorted to research carried out by Gomes (2005) in the field of Ethnic-Racial Relations, Cavalleiro (2001) and his proposals for an Anti-racist Education and Almeida (2019) in the recurrent studies to understand Structural Racism.
BNCC and anti-racist education: reflections and notes on the arts curricular component
Keywords: BNCC; educação antirracista; currículo; BNCC; anti-racist; resume; CIENCIAS HUMANAS::EDUCACAO::CURRICULO